Determination of Thorium Distribution Coefficient in Clay Soil From Bangka Belitung for Radioactive Waste Management - Arya Diva Yana; Alizar Ulianas; Dadong Iskandar; Hary Sanjaya; Jon Efendi (Universitas Pendidikan Mandalika, 2026)
Radioactive waste is material contaminated by radioactive substances from nuclear activities that pose a danger to the environment and health, so controlled management is required. The purpose of this study was to test the distribution coefficient value of Bangka Belitung clay as an adsorbent to absorb thorium ions. Clay is used because of its large surface area, which helps the adsorption process of metal ions. The results of the study showed that the optimum adsorption conditions were achieved within 10 minutes with an optimum concentration of 100 ppm. Meanwhile, the results of the Langmuir isotherm analysis had a larger R2 value, namely 0.94923. This indicates that the adsorption process is more suitable for the formation of a monolayer. Based on these results, clay can be used in landfill systems to reduce the risk of groundwater pollution.